The criminal legal meaning of the terms “defenseless” and “dependent on the perpetrator” - Sarsenbayev, T.E. (Bulletin of the Karaganda University “Law Series”, 2024)
The objective of this article is to conduct a comprehensive analysis of the criminal law significance of the terms “vulnerable” and “dependent on the offender” within the framework of the criminal legislation of the Republic of Kazakhstan. This study aims to identify issues surrounding their application and to formulate recommendations for the enhancement of the existing legal framework. This article reviews the ambiguous interpretations of these terms as they appear in current criminal law texts. A comparative analysis of the terms “vulnerable” and “helpless” is presented, revealing challenges in defining the concept of “dependency on the offender”. The findings underscore the necessity for clearer legislative definitions of “vulnerable” and “dependent on the offender” to ensure consistent application of criminal law and to better protect victims’ rights. Concrete recommendations for refining legislative norms and improving law enforcement practices are proposed. Funding Statement: This scholarly article has been prepared as part of a targeted program of scientific and/or scientific-technical financing for the years 2024‒2027. It supports the implementation of the project IRN BR BR 24993217, titled “Harmonization of Legal Terminology and Linguistic Authenticity of Legal Texts in the Field of Criminal Law of the Republic of Kazakhstan”, funded by the Committee of Science of the Ministry of Science and Higher Education of the Republic of Kazakhstan.